How Behavioural Biases and Demographic Factors relate to Financial Literacy - Ika Pratiwi Simbolon; Maria Yus Trinity Irsan; Risa Fitria (President University, 2022)
The research aims to analyze the effect of factors of demography and investor behaviors on financial literacy for investors and potential investors in Indonesia. The paper used questionnaires in collecting primary data. Policymakers, investors, and other shareholders should consider the results of this study in making important policies, especially regarding investor behaviors, not all investors act rationally. Regarding the research limitations, future research can use the research object not limited to behavioral biases and demographic factors, but more to discover a research model for financial literacy determinants. Future research may study the investors in different countries to find the effect of investor characteristics on financial literacy.